Associations Between Colonic Motor Patterns and Autonomic Nervous System Activity Assessed by High-Resolution Manometry and Concurrent Heart Rate Variability - Yuan, Yuhong; Ali, M. Khawar; Mathewson, Karen J.; Sharma, Kartik; Faiyaz, Mahi; Tan, Wei; Parsons, Sean P.; Zhang, Kailai K.; Milkova, Natalija; Liu, Lijun; Ratcliffe, Elyanne; Armstrong, David; et al. (Frontiers in Neuroscience, 2020)
Abnormal colonic motility may be associated with dysfunction of the autonomic nervous system. Our aim was to evaluate if associations between colonic motor patterns and autonomic neural activity could be demonstrated by assessing changes in heart rate variability (HRV) in healthy volunteers. A total of 145 colonic motor patterns were assessed in 11 healthy volunteers by High-Resolution Colonic Manometry using an 84-channel water-perfused catheter. Motor patterns were evoked by balloon distention, a meal and luminal bisacodyl. The electrocardiogram and cardiac impedance were assessed during colonic manometry. Respiratory sinus arrhythmia (RSA) and root mean square of successive differences of beat-to-beat intervals (RMSSD) served as measures of parasympathetic reactivity while the Baevsky’s Stress Index (SI) and pre-ejection period (PEP) were used as measures of sympathetic reactivity. Taking all motor patterns into account, our data show that colonic motor patterns are accompanied by increased parasympathetic activity and decreased sympathetic activity that may occur without eliciting a significant change in heart rate. Motor Complexes (more than one motor pattern occurring in close proximity), High-Amplitude Propagating Pressure Waves followed by simultaneous pressure waves (HAPW-SPWs) and HAPWs without SPWs are all associated with an increase in RSA and a decrease in SI. Hence RSA and SI may best reflect autonomic activity in the colon during these motor patterns as compared to RMSSD and PEP. SI and PEP do not measure identical sympathetic reactivity. The SPW, which is a very low amplitude pressure wave, did not significantly change the autonomic measured employed here. In conclusion, colonic motor patterns are associated with activity in the autonomic nervous system as reflected in autonomic measures of heart rate variability. These autonomic measures may serve as proxies for autonomic neural dysfunction in patients with colonic dysmotility.